Security relations between China and the European Union : from convergence to cooperation? - Kirchner, Emil Joseph; Christiansen, Thomas, 1965-; Dorussen, Han, 1962- (New York, NY : Cambridge University Press, 2017)
Over the past decade, the EU and China have expanded their relations beyond a focus on economic and trade issues to the sphere of security. Taking a broad definition of security, a multidisciplinary approach, and a comparative perspective (including scholars from both Europe and China), this book provides an in-depth analysis of the extent to which the EU and China not only express similar threat concerns, or make declarations about joint responses, but also adopt concrete measures in the pursuance of security cooperation. In particular, the book seeks to explore a range of key themes in the field of EU-China security cooperation such as nuclear proliferation, international terrorist threats and cyber attacks. Besides providing an overview of the areas where security cooperation exists and where it does not, it also highlights the aspects of convergence and divergence and the reasons for their occurrence.
EU-China security cooperation in context / Emil J. Kirchner, Thomas Christiansen and Han Dorussen -- Chinese and EU views of military security : crafting cooperation / Simon Duke and Reuben Wong -- Regional solutions for regional conflicts? the EU, China and their respective neighborhoods / Thomas Diez, Eva Scherwitz and See Seng Tan -- Aims versus deeds : EU-China cooperation in nuclear nonproliferation / Nicola Casarini and Xinning Song -- Terrorism and organized crime : common concerns but different interests / Raphael Bossong and Lesie Holmes -- Chinese and EU climate and energy security policy / Yan Bo, Katja Biedenkopf and Zhimin Chen -- Competing or converging claims on international order? the EU, China and human security / Sebastian Harnisch and Kai He -- Civil protection : identifying opportunities for collaboration / Han Dorussen, Ling Jin and Evangelos Fanoulis -- Cybersecurity and EU-China relations / Sebastian Bersick, George Christou and Shen Yi -- The economic security dimension of the EU-China relationship : puzzles and prospects / Gustaaf Geeraerts and Weiping Huang -- Is securitizing migration a mandatory choice? : lessons from the EU and China / Men-Hsuan Chou, Els Van Dongen and Harlan Koff -- Against the odds : (considerable) convergence and (limited) cooperation in EU-China security relations / Thomas Christiansen, Emil J. Kirchner and Han Dorussen
Includes bibliographical references and index.
Keywords: National security -- European Union countries; National security -- China; European Union countries -- Foreign relations -- China; China -- Foreign relations -- European Union countries